Penyusunan Peraturan Desa tentang Anggaran Pendapatan dan Belanja Desa Berbasis Partisipasi Masyarakat di Desa Cileles, Jatinangor, Sumedang, Jawa Barat - Mutia Rahmah; Muchlis Hamdi (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2021)
The perception that has developed is community participation in the drafting of village regulations is when village regulations is being discussed and mutually agreed between the village government and the village council. This perception is not in line with the normative that community participation should start fromthe planning step for the village budgeting regulation making. This condition also applies in the preparation of a budgeting village regulation. This community service aims to increase the understanding and awareness of village officials, village agency, and the community about the importance of the role of each actor in the village budgeting regulation making and to train as well as to simulate the village budgeting regulation making to the community so that they can have skill in conveying aspirations and building agreements for village program priorities and also skill in participating both individually and organizationally. This community service method is through socialization, discussions, questions and answers related to the village budgeting regulation making, as well as sharing experiences, training, and simulations in the implementation of village meetings and village council meetings. The findings in this community service are the village government tends to provide less opportunity for the community to participate in village government activities, the motivation of the participants is not based on awareness but is still mobilization, and the capacity of the village council as an interest articulation and aggregation of the village community as well as a partner for village government in Cileles Village. This community service concludes that literacy improvement, training, and simulations can provide knowledge, change perceptions, and understand the importance of the role of each actor, the village government as a public servant, the village council as a forum for community aspirations, and the community as the object and subject of development.